Compactação em argissolo submetido ao tráfego de veículo blindado de combate - Müller, Cândida Regina (2019)
Heavy and continuous traffic from large vehicles causes soil compaction, which reduces their physical quality and increases their susceptibility to water erosion. Military training exercises with combat vehicles cause direct damage to soil and vegetation, affecting the ecosystem. A large contingent of the Brazilian Army conducts training with armored combat vehicles at the Santa Maria Instruction Field (CISM), which has been caused soil degradation. Our objective was to evaluate the effect of armored combat vehicle traffic on the physical properties of the soil. The study was conducted on an Abrupt Alisol of CISM with a history of military vehicle traffic. The effect of driving direction and traffic intensity on soil physical properties was evaluated under conditions of high soil moisture (0.3 m3 m-3 ) under (i) straight traffic of the Leopard 1 A5BR combat vehicle, with 0, 1 and 3 passes, and (ii) pivoting maneuver with 0, 1 and 2 pivots. Soil morphology, particle size distribution and organic carbon content were analyzed in the 0.00-0.10 and 0.20-0.30 m layers. Soil density, total porosity, macroporosity, microporosity, saturated soil hydraulic conductivity, penetration resistance and preconsolidation pressure were evaluated in the 0.00-0.04, 0.10-0, 14 and 0.20-0.24 m. Preconsolidation pressure of the surface layer indicated that the soil is susceptible to traffic compaction of Leopard 1A5BR if the water content is above 0.33 m3 m-3 . As soil water content was high (0.3 m3 m-3 ) at the time of traffic, only one pass and one pivoting maneuver were sufficient to increase soil penetration resistance and density and reduce soil total porosity and macroporosity in the surface layer (0.00-0.04 m).